A Radical and Virtual Innovation Center (RVIC) for Human Resource Development (HRD) - Case Study on Planning, Developing and Sustaining the Human Capital Development - Vedhathiri, Thanikachalam (Journal of Engineering Education Transformations, 2020)
Under knowledge-based economy, there is a need for developing high-performing and self-managed faculty teams (SMFTs) for undertaking consultancy projects from the states, national and global organizations. In this research work, a case study has been presented on the initiatives of high-performing teams in undertaking diverse global faculty and executive development programs under various ministries and International Development Agencies (IDAs) like Asian Development Bank, UNDP, UNESCO, USAID and World Bank even though there is no formal consultancy center for undertaking Human Resource development Center. This resulted in engaging the faculty creatively, meeting the challenges, focusing on the real-world problems, advancing the personalized learning, developing interdisciplinary master and doctoral programs. This has capitalized in brining Industry-Institute-Government-Society (I-I-G-S) Partnership and improved the competitiveness of the nation. Even though there is Technical Teachers Training Institute (TTTI), Chennai was established in 1964 primarily for developing the polytechnics through faculty development in 1964. Under Quality Improvement Program (QIP) of the Government of India, Curriculum Evaluation, Improvement, and Development of new programs based on the emerging technologies have been undertaken. Further to assist the faculty, Instructional Material Production was undertaken. Long-term Programs like Diploma in Technical Teaching (Dip. T.T.), Diploma in Science Teaching (Dip. Sc.), and Bachelor of Technical Education (B. Tech. Ed.) were established. To meet the needs of many specializations, Certificate courses in Technical Teaching (Cert. T.T.), and Educational Technology (Cert. E.T.) were introduced. Based on the needs of various states, Extension Centers have been established in Kalamassery for Kerala, Hyderabad neither an established Consultancy Center nor a Department for HRD, the Self-Managed and High-Performing Faculty Team established a Radical and Virtual Innovation Center (RVIC) for Human Resource Development with an ultimate global focus and interdisciplinary programs and diverse global human resource development programs. Some of these programs are not only helping the nation to achieve the sustainable goals identified by the United Nations, but also Peace Engineering Education. Ultimately the RVIC has to be institutionalized for harnessing continued benefit not only the institute but also to the diverse global participants.